Correction: Akram, M.N.; Abdul-Kader, W. Repurposing Second-Life EV Batteries to Advance Sustainable Development: A Comprehensive Review. Batteries 2024, 10, 452 - Muhammad Nadeem Akram; Walid Abdul-Kader (Batteries)
The authors wish to make the following corrections to their paper [...]